MONITORING OF SURFACE DISPLACEMENTS IN THE KALOCHORI AREA (THESSALONIKI, GREECE) USING A LOCAL GNSS NETWORK - Ganas, A.; Chousianitis, K.; Argyrakis, P.; Tsimi, Ch.; Papanikolaou, M.; Papathanassiou, G.; Exarchos, K. (Bulletin of the Geological Society of Greece, 2016)
The ground motions in the Kalochori region (well known for its subsidence history during the 2nd half of 20th century) were investigated by NOA using a mobile GNSS (GPS) network, comprising 18 stations. The network was measured four (4) times during the period October 2013 - April 2015 under the framework of the research project INDES-MUSA. Our GPS measurements were processed with GAMIT software and show vertical (ITRF 2008) motions ranging from -2 cm to +2 cm (i.e. just above the margins of measurement error) with the exception of the Kalochori dam where an uplift of 2-5 cm was observed. We also found no evidence for local (non-tectonic) motions and/or interseismic strain.